Diastereoselective Synthesis of Chiral Oxathiazine 2‐Oxide Scaffolds as Sulfinyl Transfer Agents. Issue 10 (22nd April 2022) - Quintavalla, Arianna; Veronesi, Ruben; Zambardino, Demetra; Carboni, Davide; Lombardo, Marco
Abstract: An efficient diastereoselective route for the preparation of chiral oxathiazine 2‐oxide scaffolds as sulfinyl transfer agents, using tert ‐butanesulfinamide ( t BSA) both as the source of chirality and as the precursor to the required nitrogen electron withdrawing group on the scaffold, was developed. This methodology allows the introduction of different substituents on the chiral scaffold, using commercially available reagents and standard synthetic transformations. The synthesized scaffolds were tested in the preparation of enantioenriched sulfinamides, providing results comparable to the sulfinyl transfer agents so far proposed in the literature, and opening the possibility to further elaborate these scaffolds, with the aim to support them on solid phases so to facilitate their recovery and reuse. Abstract :